Low Back Pain Prevalence and Associated Factors in Iranian Population: Findings from the National Health Survey. (11th September 2012) - Biglarian, Akbar; Seifi, Behjat; Bakhshi, Enayatollah; Mohammad, Kazem; Rahgozar, Mehdi; Karimlou, Masoud; Serahati, Sara
Abstract : Background . There are very few studies that had a sample size sufficient to explore the association between factors related to low back pain in a representative sample of the Iranian population. Objective . To examine the relationship between sociodemographic factors, smoking, obesity, and low back pain in Iranian people. Methods . We used Iranian adults respondents (n = 25307 ) from the National Health Survey. Adjusted odds ratios and 95% confidence intervals were estimated by using logistic regression. Results . The prevalence of low back pain was found in 29.3% of the studied sample. High age, female sex, being married, obesity, low-economic index, being smoker, in a rural residence, and low educational attainment, all increased the odds of low back pain. Conclusions . Our findings add to the evidence on the importance of obesity in relation to low back pain. These results can be used as a basis to reinforce health programs to prevent obesity.